Assessment of Irrigation Water Quality in District Attock, Pakistan: Assessment of Irrigation Water Quality (Biological Sciences - PJSIR, 2015)
Water samples (total 277) were collected during previous three years (2008-09 to 2010-11) from all tehsils of Attock district, Pakistan, used for irrigation purpose. Regarding sources of irrigation, 122 samples were collected from bores (turbine operated), 97 from wells, 19 from nullahs and 39 from dams. The analysis data showed that 120 samples (43%) were fit, 35 samples (13%) were marginally fit, while 122 samples (44%) were unfit. As regards minimum and maximum range, it varied in EC from 0.05 to 8.1 dS/m, calcium plus magnesium from 0.6 to 70 meq/L, sodium from zero to 40.6 meq/L, carbonates from zero to 0.04 meq/L, bicarbonates from 0.5 to 15 meq/L, chlorides from 0.2 to 70 meq/L, sodium adsorption ratio from zero to 49.85 and residual sodium carbonate from zero to 13 meq/L. Recommendations for wise and judicious use of marginally fit to unfit irrigation water were imparted to the farmers for raising different arable, fruit and vegetable crops.